The Role of Transformational Leadership in Improving Service Quality at Ophthalmology Clinics - Aisyah Khairunnisa; Nuri Herachwati; Zuyyinna Choirunnisa (Penerbit Goodwood, 2026)
Purpose: This systematic review examines the influence of transformational leadership on service quality in ophthalmology clinics, focusing on key metrics such as clinical accuracy, efficiency, and technological adoption. Research Methodology: A comprehensive search was conducted across PubMed, Scopus, and Web of Science for peer-reviewed studies (2010–2024) linking TL to service quality in ophthalmology or analogous specialty clinics. Data were synthesized thematically, and findings were assessed for consistency and applicability using the PRISMA guidelines. Results: Preliminary analysis indicates that TL positively impacts service quality through (1) staff motivation to adhere to clinical protocols, (2) fostering innovation in diagnostic technologies, and (3) optimizing operational workflows to reduce delays. However, evidence specific to ophthalmology remains limited, highlighting the research gap. Conclusions: These findings on how transformational leaders foster a work environment centered on learning, innovation, and collaboration align with the demands of modern value-based healthcare, which requires the integration of technical excellence and patient experience Limitations: The limitations of this systematic review include potential inconsistencies due to varying definitions and measurements of transformational leadership and service quality, possible publication bias from relying solely on available published literature, restricted generalizability beyond ophthalmology clinics, and the challenge of drawing universal conclusions due to differing cultural and organizational contexts across studies. Contributions: This study specifically focuses on ophthalmology, providing insights relevant to eye care administrators. This study bridges the gap between general leadership theory and its practical application in high-demand clinics.